2017
DOI: 10.3233/bmr-160536
|View full text |Cite
|
Sign up to set email alerts
|

The relation between chondromalacia patella and meniscal tear and the sulcus angle/ trochlear depth ratio as a powerful predictor

Abstract: An increased trochlear sulcus angle/trochlear depth ratio is a significant predictor of chondromalacia patella. Medial meniscus injury is more prevalent in patients with chondromalacia patella in association with impairment in knee biomechanics and the degenerative process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 21 publications
1
23
3
1
Order By: Relevance
“…Although it has been suggested that a wide variety of factors including trauma, anatomical predisposition, patellofemoral malalignment, and overuse contributes to the formation of CMP, the actual cause of CMP has not been clarified 6. In several recent studies, the relation between CMP and knee morphometric and alignment measurements in young adults has been evaluated 5,7891011. CMP has also been associated with the formation of edema in the superolateral region of the Hoffa's fat pad (SHFP) 8.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been suggested that a wide variety of factors including trauma, anatomical predisposition, patellofemoral malalignment, and overuse contributes to the formation of CMP, the actual cause of CMP has not been clarified 6. In several recent studies, the relation between CMP and knee morphometric and alignment measurements in young adults has been evaluated 5,7891011. CMP has also been associated with the formation of edema in the superolateral region of the Hoffa's fat pad (SHFP) 8.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 18 One recent study proposed the sulcus angle/trochlear depth ratio as a powerful predictor. 11 One limitation of our study is that patellar and trochlear morphology were not evaluated. Another limitation is that due to its retrospective nature patients were not assessed in terms of diabetes during the study.…”
Section: Discussionmentioning
confidence: 97%
“…Trauma, degenerative changes, morphological variations, mechanical stress impairments and aging are factors involved in the etiology of OA, CP, bursitis and medial meniscal tear. 3 , 11 Common risk factors are one of the reasons why pathologies in the knee joint affect more than one anatomical structure, rather than remaining local. Moreover, pathologies that begin locally induce morphological and functional changes in other anatomical structures by compromising biomechanics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patellofemoral eklem problemlerin tanısında hâlâ bilinmeyen birçok nokta mevcuttur. Tanıda kullanılan metotların güvenilirliği literatürde tartışılmıştır (27,28). Günümüzde hâlen dinamik Bilgisayarlı Tomografi (BT) ve MRG patellofemoral eklemin dizilim bozukluğunun analizinde geniş kullanım alanı bulmuştur (29).…”
Section: P-pt (°)unclassified